Desain perkotaan peka iklim dalam lanskap budaya - Rina Kurniati; Wakhidah Kurniawati; Diah Intan Kusumo Dewi; Endah Kartika Syahri (Program Studi Arsitektur Fakultas Teknik Universitas Katolik Widya Mandira, 2023)
Climate Sensitive Urban Design (CSUD) is a new paradigm in urban planning that is adaptive to climate change by adapting various elements that support the physical development. This study aims to determine the appropriate landscape design adjustment strategy in cultural landscape such as the Old Town Semarang. The data used are in the form of six CSUD components such as air temperature and thermal comfort, vegetation, shadows, materials, solar radiation, and frequency of regional activities. Data processing is carried out by simulating CSUD elements such as shadows, vegetation, and solar radiation using the Sunhour and Curic Sun menus in the Sketchup application. To determine the significant effect between test variables, the SPSS linear regression analysis method was used. The results obtained are several scenarios for the proper application of CSUD at four stations in the Old Town Semarang. The findings are in the form of the influence of the presence of vegetation and shadows of objects in minimizing heat stress. The addition of 1% shadow area can increase the area with moderate to low radiation levels by 1.083%..